Effect of abdominal massage and comprehensive nursing on relieving constipation in elderly patients with diabetes (腹部推拿治疗糖尿病便秘效果观察及护理) - YAN Qiuyan (闫秋艳); LIU Fei (柳菲) (中西医结合护理)
Objective To investigate the effect of abdominal massage on relieving constipation in elderly patients with diabetes, and summarize comprehensive nursing measures during the treatment. Methods Totally 80 elderly diabetic patients with constipation were randomly divided into the control group and observation group, with 40 cases in each group. All patients were given glucose-lowering Therapy and routine care, and Traditional Chinese Medicine abdominal massage was carried in the observation group. The constipation index, Patient Assessment of Constipation Quality of Life scale(PAC-QoL) and patient satisfaction were measured and compared between two groups. Results The constipation index score decreased in both two group after intervention, and constipation index score in the observation group was lower than that in the control group (P＜0. 01). The PAC-QoL score decreased in both two group after intervention, and PAC-QoL score in the observation group was lower than that in the control group (P＜0. 01). The satisfaction rate in the observation group was higher than that in the control group(P＜0. 05). Conclusion Based on the comprehensive nursing interventions, the abdominal massage is effective to relieve constipation symptoms and improve the quality of life in elderly patients with diabetes. (目的 探讨中医腹部推拿治疗糖尿病便秘的效果, 总结治疗期间综合护理干预措施。方法 选择2021年6月—2022年6月医院收治的糖尿病便秘患者80例, 随机分为对照组和观察组, 各40例。两组均接受常规降糖治疗, 对照组治疗期间接受常规护理, 观察组在对照组基础增加中医腹部推拿治疗。 采用便秘指数评价患者症状改善情况, 采用便秘患者生活质量问卷(PAC-QoL)评价患者生活质量, 采用自制量表评价患者满意度。结果 干预后, 两组便秘指数评分较干预前下降, 且观察组便秘指数评分低于对照组, 差异有统计学意义(P＜0. 01)。干预后, 两组PAC-QoL量表分较干预前下降, 且观察组PAC-QoL量表评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 在综合护理干预的基础上, 中医腹部推拿够迅速改善糖尿病便秘患者的便秘症状, 改善生活质量, 提升护理满意度。)